Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Antimycobacterial labdane diterpenes from leucas stelligera - Kulkarni, Roshan R.; Shurpali, Ketaki; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Journal of Natural Products, 2013)
Phytochemical investigation of the acetone extract of the aerial parts of Leucas stelligera afforded four new compounds (1-4) belonging to the labdane diterpene series as well as two known flavones, velutin (5) and chrysoeriol (6). Structure elucidation of the new compounds was carried out using ID and 2D NMR spectroscopic data and single-crystal X-ray crystallography of compound 1. Compounds 1-4 exhibited selective antimycobacterial activity against Mycobacterium tuberculosis with IC50 values in the range 5.02-9.80 mu g/mL.

Lavandula gibsoni and plectranthus mollis essential oils: chemical analysis and insect control activities against aedes aegypti, anopheles sfttephensi and culex quinquefasciatus - Kulkarni, Roshan R.; Pawar, Pushpa V.; Joseph, Mary P.; Akulwad, Ambadas K.; Sen, Avalokiteswar; Joshi, Swati P. (Journal of Pest Science, 2013)
Essential oils and acetone extracts from Lavandula gibsoni and Plectranthus mollis, family Lamiaceae, were investigated for their mosquito larvicidal activity against 4th instar larvae of Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus. LC50 values against these three species were 48.3, 62.8 and 54.7 mg/L for L. gibsoni essential oil and 118.5, 137.2 and 128.1 mg/L, respectively, for its acetone extract, while LC50 values for P. mollis essential oil were 25.4, 33.5 and 29.5 mg/L and 195.0, 213.8 and 209.0 mg/L, respectively, for its acetone extract. Repellence of the essential oils was assessed against A. aegypti adults. L. gibsoni essential oil provided 100 % protection for more than 7 h at a concentration of 2.0 mg/cm(2). Under the same conditions, the standard repellent N,N-diethyl-meta-toluamide, at 0.25 mg/cm(2), provided 100 % protection for more than 8 h, while P. mollis essential oil was only weakly repellent. The major components from both essential oils were identified based on GC-MS analysis and linear retention indices. Our results demonstrated promising larvicidal activities of both essential oils against these mosquito species. L. gibsoni essential oil also showed promising repellent activity.
Keywords: Essential oil; Lavandula gibsoni; Mosquito larvicidal activity; Mosquito repellent; Plectranthus mollis

New 2,2-diphenylpropane and ethoxylated aromatic monoterpenes from Lavandula gibsoni (Lamiaceae) - Kulkarni, Roshan R.; Joshi, Swati P. (Natural Product Research, 2013)
A new substituted 2,2-diphenylpropane (1) and two new ethoxylated aromatic monoterpene alcohols (2 and 4) have been isolated from the acetone extract of the aerial parts of Lavandula gibsoni, along with the known compounds 8-hydroxycarvacrol (3), 8-hydroxythymol (5), coumarin (6), 4-methylresorcinol (7), 7,4-dimethylapigenin (8), salvigenin (9), -sitosteryl-3-O–D-glucopyranosyl-6-O-palmitate (10) and euscaphic acid D (11). The structures of the isolated compounds were assigned on the basis of their H-1- and C-13-NMR spectra and two-dimensional NMR techniques, which included COSY, HSQC, HMBC and NOESY experiments and comparison with the reported literature.
Keywords: 2; 2-diphenylpropane; aromatic monoterpene alcohols; Lamiaceae; Lavandula gibsoni

Antifungal dimeric chalcone derivative kamalachalcone E from Mallotus philippinensis - Kulkarni, Roshan R.; Tupe, Santosh G.; Gample, Suvarna P.; Chandgude, Macchindra G.; Sarkar, Dhiman; Deshpande, Mukund V.; Joshi, Swati P. (Natural Product Research, 2014)
From the red coloured extract (Kamala) prepared through acetone extraction of the fresh whole uncrushed fruits of Mallotus philippinensis, one new dimeric chalcone (1) along with three known compounds 1-(5,7-dihydroxy-2,2,6-trimethyl-2H-1-benzopyran-8-yl)-3-phenyl-2-propen -1-one (2), rottlerin (3) and 4 `-hydroxyrottlerin (4) were isolated. The structure of compound 1 was elucidated by 1D and 2D NMR analyses that included HSQC, HMBC, COSY and ROESY experiments along with the literature comparison. Compounds 1-4 were evaluated for antifungal activity against different human pathogenic yeasts and filamentous fungi. The antiproliferative activity of the compounds was evaluated against Thp-1 cell lines. Compounds 1 and 2 both exhibited IC50 of 8, 4 and 16 mu g/mL against Cryptococcus neoformans PRL518, C. neoformans ATCC32045 and Aspergillus fumigatus, respectively. Compound 4, at 100 mu g/mL, showed 54% growth inhibition of Thp-1 cell lines.
Keywords: 4 `-hydroxyrottlerin; antifungal; dimeric chalcone; kamalachalcone E; Mallotus philippinensis; rottlerin

Rottlerin derivatives and other compounds from mallotus philippinensis fruits and their potential antimycobactrial activity - Bhardwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae